Efficacy and safety of a multifactor intervention to improve therapeutic adherence in patients with chronic obstructive pulmonary disease (COPD): protocol for the ICEPOC study - Barnestein-Fonseca, Pilar; Leiva-Fernández, José; Vidal-España, Francisca; García-Ruiz, Antonio; Prados Torres, Daniel; Leiva-Fernández, Francisca (BIOMED CENTRAL LTD, 2011)
Our study will evaluate the effectiveness of a multifactor intervention to improve the therapeutic adherence of COPD patients. Methods/Design: A randomized controlled clinical trial with 140 COPD diagnosed patients selected by a nonprobabilistic method of sampling. Subjects will be randomly allocated into two groups, using the block randomization technique. Every patient in each group will be visited four times during the year of the study. Intervention: Motivational aspects related to adherence (beliefs and behaviour): group and individual interviews; cognitive aspects: information about illness; skills: inhaled technique training. Reinforcement of the cognitiveemotional aspects and inhaled technique training will be carried out in all visits of the intervention group. Discussion: Adherence to a prescribed treatment involves a behavioural change. Cognitive, emotional and motivational aspects influence this change and so we consider the best intervention procedure to improve adherence would be a cognitive and emotional strategy which could be applied in daily clinical practice. Our hypothesis is that the application of a multifactor intervention (COPD information, dose reminders and reinforcing audiovisual material, motivational aspects and inhalation technique training) to COPD patients taking inhaled treatment will give a 25% increase in the number of patients showing therapeutic adherence in this group compared to the control group.
Keywords: Enfermos de Enfermedad pulmonar obstructiva crónica - Psicología; EPOC; Adherence